Pengembangan E-LKPD Berbasis Problem Based Learning Materi Sistem Ekskresi Kelas XI - Chairunnisa Aulia Utami Harahap; Fitra Suzanti; Sri Wulandari (LPPM Institut Pendidikan Nusantara Global, 2026)
The rapid development of information technology has increased the number of computer and internet users, which encourages science learning in the classroom to educate students about science and technology. In the 21st century, the use of technology in education is important to encourage students to learn independently, collaboratively, creatively, and critically. One innovation in learning is the use of E-LKPD (Electronic Student Worksheet), which is designed to replace printed LKPD which tends to be boring. The material on the excretory system in grade XI is considered difficult and less interesting for students, so it is necessary to develop E-LKPD based on problem based learning to improve student understanding. This study uses the ADDIE model which consists of five stages: analysis, design, development, implementation, and evaluation, but this study only reaches the development stage. The developed E-LKPD was validated by four validators and tested on students and grade XI students of SMA Muhammadiyah 1 Pekanbaru. The validation results showed an average score of 3.70 (very valid category), while the trials of stages I and II each scored 3.63 and 3.61 (very good category). In conclusion, E-LKPD based on problem based learning for excretory system material for grade XI was successfully developed and is suitable for use as a learning resource.